Oblique thrusting and strain partitioning in the Longmen Shan fold‐and‐thrust belt, Eastern Tibetan Plateau - Li, Zhigang (2018)
Eastern Tibet is an important example of oblique convergence and associated strain partitioning, as suggested by recent 2‐D and 3‐D structural interpretations, yet the nature and evolution of oblique strain partitioning of this region remain poorly known. Here we use seismic reflection profiles, borehole data, and field investigations in the Longmen Shan piedmont to determine the subsurface structural architecture, and we observe several nearly N‐S striking thrusts and reactivation of NE striking preexisting faults. We interpret that this behavior is due to a regional principal compressional stress oriented in the E‐W direction, oblique to the NE striking Longmen Shan. Using the records of fault activity and related Late Pliocene and Quaternary foreland sediments and growth strata, as well as the coseismic rupture of the 2008 Mw 7.9 Wenchuan earthquake, we demonstrate that the Longmen Shan has experienced E‐W crustal shortening and oblique motion since ~5–2 Ma. We present two strain partitioning models arising from oblique thrusting in eastern Tibet and suggest that the eastward extrusion from Tibet is mainly accommodated on the strike‐slip Longriba fault and the dip‐slip Longmen Shan‐Min Shan fault zones. These results enhance our understanding of the tectonic relationship between the Songpan‐Ganzi terrane and the Sichuan basin and provide additional constraints for studies of the geodynamic response of eastern Tibet to the ongoing India‐Eurasia collision.